First description of the larva and pupa of the coconut palm borer Homalinotus depressus (Linnaeus, 1758) (Coleoptera: Curculionidae: Molytinae) and a discussion about the terminology for immature forms - Lira, Aline De Oliveira; Rosado-Neto, Germano Henrique; Marques, Marinêz Isaac; Sousa, Wesley Oliveira De (Zootaxa, 2017)
Homalinotus depressus (Linnaeus, 1758) (Molytinae: Cholini) is an economically important weevil that occurs in association with wild palm trees and causes damage to coconut plantations (Cocus nucifera L.) in the state of Pará, Brazil. We present, for the first time, descriptions and illustrations of the larva and pupa of H. depressus, with discussion of the terminology used for morphology and chaetotaxy of Curculionoidea. We compare the descriptions of the immature stages of Homalinotus depressus with descriptions of larvae and pupae of Heilipodus erythropus (Klug, 1829) (Hylobiini), Rhyparonotus altarensis   (Olliff, 1891) (Anchonini) and Pissodes Germar, 1817 (Pissodini) species belonging to Molytinae.